Immunological risk assessment: The key to individualized immunosuppression after kidney transplantation - Pratschke, Johann; Schemmer, Peter (Transplantation reviews, 2016)
The wide range of immunosuppressive therapies and protocols permits tailored planning of the initial regimen according to the immunological risk status of individual patients. Pre-transplant risk assessment can include many factors, but there is no clear consensus on which parameters to take into account, and their relative importance. In general younger patients are known to be at higher risk for acute rejection, compounded by higher rates of non-adherence in adolescents. Donor age and recipient gender do not appear to exert a meaningful effect on risk of rejection per se, but black recipient ethnicity remains a well-established risk factor even under modern immunosuppression regimens. Little difference in risk is now observed between deceased- and living-donor recipients. Immunological risk assessment has developed substantially in recent years. Cross-match testing with cytotoxic analysis has long been supplemented by flow cytometry, but development of solid-phase single-bead antigen testing of solubilized human leukocyte antigens (HLA) to detect donor-specific antibodies (DSA) permits a far more nuanced stratification of immunological risk status, including the different classes and intensities of HLA antibodies Class I and/or II, including HLA-DSA. Immunologic risk evaluation is now often based on a combination of these tests, but other assessments are becoming more widely introduced, such as measurement of non-HLA antibodies against angiotensin type 1 (AT1) receptors or T-cell ELISPOT assay of alloantigen-specific donor. Targeted densensitization protocols can improve immunological risk, notably for DSA-positive patients with negative cytotoxicity and flow cross-match. HLA mismatch remains an important and undisputed risk factor for rejection. Delayed graft function also increases the risk of subsequent acute rejection, and the early regimen can be modified in such cases. Overall, there is a shift towards planning the immunosuppressive regimen based on pre-transplant immunology testing although certain conventional risk factors retain their importance.
Gesehen am 22.11.2019